Implementasi Ajaran Ketamansiswaan Tri-Nga untuk Menanamkan Budi Pekerti Luhur dalam Perkuliahan Pendidikan Kewarganegaraan - Nadziroh Nadziroh (Taman Cendekia: Jurnal Pendidikan Ke-SD-an, 2017)
The purpose of this research is to get better understanding about the implementation process of Tri-Nga to instill a sense of Nobel Character in Civic Education subject and student activities in implementing Tri-Nga to instill a sense of nobel character in Civic Education class. This is a type of qualitative research. The data of this study are gained from the activities of students who attend civic education class, which is implicitly delivering nobel character value. The instrument in this study is the research itself, which is supported by the interview guidelines, observation, and documentation. The data analysis technique used in this research refers to data analysis technique developed By Moleong. Data validity checking used is the degree of trust (credibility). The result of data analysis showed that the students have implemented nobel character by applying Tri-Nga theory in a good way. The development of nobel character was implemented in the Civic education class through cognitive moral approach, instillation a sense of value approach, and value clarification approach. Students’ activities in Tri-Nga implementation on Civic education class in which the students are aware of knowing it, realizing it and believing in it, would carried out the following moral values: 1). Possessing and developing tolerance, 2). Growing the self-discipline, 3). Developing work ethic, 4). Having a sense of responsibility, 5). Having a sense of being open to others, 6). Being able to think positively, 7). Developing self-potention, 8). Having togetherness and mutual cooperation, 9). Having mutual respect, and 10). Growing honesty.